Neurofeedback bei Kindern mit ADHS - Welche Wirkungen sind zu erwarten? Stand der Forschung und Anregungen für die Praxis - Strehl, Ute; Heinrich, Hartmut; Rothenberger, A.; Gevensleben, H. (Pädiatrische Praxis, 2019)
EEG neurofeedback is a possible complementary procedure for the treatment of ADHD. It is based on observations that children with ADHD exhibit physiologically hypoarousal of brain activity. Standard protocols in the frequency band (theta/beta, SMR) or event-related brain activity (Slow Coetical Potentials, SCP) have been investigated in a number of studies. They suggest that NF, using standard protocols and a neurobehavioral approach, is a specific, effective and evidence-based component for the treatment of children with ADHD. Open questions, which aim at a better understanding of the mechanisms of action and in particular at the optimisation and individualisation of training, must be pursued further.
CRIS-Team Scopus Importer:2021-04-20
Keywords: ADHD; Efficacy; Methodical basis; Neurofeedback; Practical application